2008
DOI: 10.1158/0008-5472.can-07-1336
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Endoplasmic Reticulum Stress and Akt with OSU-03012 and Gefitinib or Erlotinib to Overcome Resistance to Epidermal Growth Factor Receptor Inhibitors

Abstract: Preexisting and acquired resistance to epidermal growth factor receptor (EGFR) inhibitors limits their clinical usefulness in patients with advanced non-small cell lung cancer (NSCLC). This study characterizes the efficacy and mechanisms of the combination of gefitinib or erlotinib with OSU-03012, a celecoxib-derived antitumor agent, to overcome EGFR inhibitor resistance in three NSCLC cell lines, H1155, H23, and A549. The OSU-03012/EGFR inhibitor combination induced pronounced apoptosis in H1155 and H23 cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 49 publications
(42 reference statements)
8
53
0
Order By: Relevance
“…However, as drug resistance ultimately occurs, patients with poor prognosis have made up a considerable part. 42,45 Our data showed a significant deactivation of this signaling pathway, which may imply a more widely downregulatory effect. Thus, chemotherapy triggering ER stress for the cancer induced by hyperactivated AKT may be helpful for overcoming drug resistance.…”
Section: -34mentioning
confidence: 58%
See 1 more Smart Citation
“…However, as drug resistance ultimately occurs, patients with poor prognosis have made up a considerable part. 42,45 Our data showed a significant deactivation of this signaling pathway, which may imply a more widely downregulatory effect. Thus, chemotherapy triggering ER stress for the cancer induced by hyperactivated AKT may be helpful for overcoming drug resistance.…”
Section: -34mentioning
confidence: 58%
“…39 Our study here revealed that the deactivation of AKT, as a downstream event of ER stress, led to the suppression of mTOR thus inducing autophagy. Interestingly, while large number of evidence support that ER stress downregulates AKT activity, 38,[40][41][42][43] it was also reported that AKT and ERK are rapidly activated and act as downstream effectors of PI3K in acute ER stress. 44 Considering that AKT and MAPK pathways are two major survival signaling cascades, cells may activate them through UPR to transmit survival signals and overcome the adverse condition, when ER stress is moderate and recoverable.…”
Section: -34mentioning
confidence: 99%
“…OSU-03012 has been shown to induce apoptosis in non-small cell lung cancer (26) and breast cancer cells (27,28) through inhibition of PDK/AKT signaling pathway. However, only very limited PDK1 and AKT inhibition were detected in OSU-03012-treated Huh7 cells in this study, suggesting that OSU-03012 suppresses the growth of Huh7 cells through a mechanism different from PDK1 and AKT inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Equivalent amounts of proteins (,10 ng) were resolved by SDS-PAGE and then transferred to nitrocellulose membranes for immunoblotting as described previously (Wang et al, 2008b). The primary antibodies (SOX17 and CDH1) used here were the same as used for immunocytochemistry.…”
Section: Western Blot Assaymentioning
confidence: 99%